Early Childhood Education, structural racism and capitalism (TEL Tempo, Espaço e Linguagem, 2026)
Using historical method, the article focuses on the financing of early childhood education. It proposes inextricable links between dependent capitalism, structural racism and educational inequality for black children. It highlights how, throughout history, black children have been discriminated against for not recognizing their full humanity and their relationships with public policies. It highlights movements in favor of public education, and the achievements of the 1988 Constitution. It discusses funding after 1988, Fundeb and highlights the obstacles of austerity. It concludes by highlighting the social struggles committed to truly universal public education, hoping that racial and social inequalities can be overcome.